Performance of Xpert® MTB/RIF in detecting Multidrug-Resistance Tuberculosis in West Java, Indonesia (Majalah Kedokteran Bandung, 2020)
Indonesia is the 2nd country with the highest tuberculosis (TB) caseload in the world. Inappropriate TB treatment may lead to multidrug-resistance tuberculosis (MDR-TB) development. TB rapid detection is important, and very much needed, to prevent transmission and deaths due to this disease. The Xpert® MTB/RIF is proposed to address this problem. This study aimed to assess the performance of the Xpert® MTB/RIF test in West Java, Indonesia. This was a cross-sectional study conducted on MDR-TB suspects referred to Dr. Hasan Sadikin General Hospital Bandung, West Java, Indonesia, using data from the eTB Manager. The performance of Xpert® MTB/RIF testing and its validity was tested against conventional drug susceptibility testing (DST). In total, data from 4,452 MDR-TB suspects were retrieved but only 578 data that had both DST and Xpert® MTB/RIF results were included in the study. The Xpert® MTB/RIF showed a sensitivity of 88% (95%CI: 85%-91%), specificity of 66% (95%CI: 60%-72%), positive predictive value of 79% (95%CI: 75%-83%), and negative predictive value of 80% (95%CI: 74%-85%), with a detection accuracy of 79%. Xpert® MTB/RIF test in this study shows a good performance for the diagnosis of MDR-TB when compared to the Mycobacterium tuberculosis culture as the gold standard. Therefore, rapid Xpert® MTB/RIF examination is recommended for MDR-TB screening for countries with a high TB burden as a complementary tool to the reference standard test. Performa Xpert® MTB/RIF Dalam Mendeteksi Tuberculosis Resisten Obat di Jawa Barat, IndonesiaIndonesia adalah negara ke-2 dengan jumlah kasus tuberkulosis (TB) tertinggi di dunia. Pengobatan TB yang tidak sesuai dapat mengakibatkan kuman TB menjadi resisten terhadap obat TB yang disebut TB multidrug-resistances (TB-MDR). Untuk itu diperlukan alat deteksi yang mumpuni sehingga kuman TB-DR dapat segera didiagnosis dan diberikan pengobatan yang tepat; dengan demikian pencegahan dan kematian akibat TB dapat ditekan. Penelitian ini bertujuan untuk mengukur performa mesin Xpert® MTB/RIF dalam mendeteksi kuman TB-MDR di Jawa Barat, Indonesia. Studi potong lintang dilakukan dengan mengambil data dari 4452 pasien terduga TB-MDR yang terregistrasi di eTB Manager selama tahun 2012-2016 yang dikirim ke Rumah Sakit Dr. Hasan Sadikin Bandung. Walaupun demikian, hanya 578 yang memiliki hasil test kultur untuk mengetahui sensitivitas obat TB. Dari kedua test tersebut, didapatkan Xpert® MTB/RIF memiliki sensitivitas 88% (95% IK: 85%-91%), spesifisitas 66% (95%CI: 60%-72%), positive predictive value 79% (95% IK: 75%-83%), dan negative predictive value 80% (95% IK: 74%-85%), dengan akurasi 79%. Test TB-MDR menggunakan Xpert® MTB/RIF pada penelitian ini menunjukkan performa yang baik, sehingga test ini sangat direkomendasikan untuk deteksi TB-MDR yang cepat, utamanya di daerah dengan prevalensi TB yang tinggi.
Keywords: MDR-TB; Sensitivity; Specificity; XpertÂ® MTB/RIF